EXAMINING A SPEAKING SYLLABUS AT TERTIARY LEVEL - Susiati, S (Universitas Muhammadiyah Surakarta, 2017)
This study examines how a Speaking syllabus at tertiary level meets the students needs through debating activity. Employing Browns (1995) and Richards (2001) theories as the main stake, six elements of the syllabus have been investigated that are needs analysis, objectives, language learning philosophy, methodology, materials used and resources and evaluation. It has been found that some revisions of the syllabus are needed to satisfy the Departments vision that prepares the students to be English teachers. However, both debating materials and activities seem to be useful for improving the students critical thinking. Of all the elements, material resources are considered the weakest part of the syllabus since it provides less appropriate references.